2008
DOI: 10.1007/s10551-008-9763-7
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Leadership, Ethics and the Challenges of Marketing Fair and Ethical Trade

Abstract: affinity marketing, ethical leadership, fair trade movement, marketing ethics, no-sweat movement, zoos, aquaria, sweat shops, ethical purchasing, virtue ethics, conservation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 24 publications
0
42
0
1
Order By: Relevance
“…The ethical spaces provided by the NCCs offer individuals a less constrained choice supported by 'affinity relationships' (Low and Davenport, 2009) that develop within the community. Following McKenzie-Mohr (1999), all the researched communities apart from Fallowfields can be seen as effective cases of what the author terms community-based social marketing.…”
Section: Resultsmentioning
confidence: 99%
“…The ethical spaces provided by the NCCs offer individuals a less constrained choice supported by 'affinity relationships' (Low and Davenport, 2009) that develop within the community. Following McKenzie-Mohr (1999), all the researched communities apart from Fallowfields can be seen as effective cases of what the author terms community-based social marketing.…”
Section: Resultsmentioning
confidence: 99%
“…Some examples include cases of nonprofit organizations buying fair trade products (Low & Davenport, 2009), or motivations to buy renewable electricity (Wiser, Fowlie, & Holt, 2001), or the use of sustainable timber in projects (Zuo, Potangaroa, Wilkinson, & Rotimi, 2009). More recently, Meehan and Bryde (2011) have concluded from a survey to Housing…”
Section: Introductionmentioning
confidence: 99%
“…Townsend (2009) briefly mentioned some sustainable food issues, such as seafood and animal welfare, within the wider context of zoo sustainability but did not discuss the issues in detail. Low and Davenport (2009) found that zoo catering facilities generally exhibited a higher level of sustainable procurement than zoo retail outlets, perhaps because of greater choice editing. Chester Zoo's Café Tsavo, for example, implemented SFP practices and noted reductions in food miles and food waste, as well as a greater incidence of locally supplied and fairly traded products (Davies, 2007).…”
Section: Sustainable Food Supply Chains In Zoosmentioning
confidence: 98%